DI BALIK AKUNTABILITAS KEUANGAN POLISI: STUDI FENOMENOLOGIS TENTANG ICFR DI POLDA SULAWESI UTARA - Albuhari, Qamaria N. Rahmatia; Kaligis, Stevie; Syaefudin, Fanessa I.M. (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose - This study examines the quality of ICFR/PIPK at the Financial Division of the North Sulawesi Regional Police and explores how financial officers interpret its implementation in supporting public financial accountability. Methods - Using a qualitative phenomenological approach, data were collected through semi-structured interviews, non-participant observation, and documentation involving financial officers selected through purposive sampling with a gatekeeper. Data were analyzed thematically using data reduction, data display, conclusion drawing, and a thematic matrix. Findings - The findings show that ICFR/PIPK has been implemented fairly well through regulatory compliance, technical guidance, team assignment, documentation, reconciliation, verification, and hierarchical reporting. However, implementation remains constrained by limited personnel, uneven understanding, input errors, delayed data submission, coordination issues, and weak risk-based control. Research Implications - The study recommends integrating ICFR/PIPK into the police command structure, strengthening PIPK focal points, and aligning reporting with Puskeu Presisi and SAKTI. Originality - This study offers a phenomenological understanding of ICFR/PIPK in a police institution.